2015
DOI: 10.1016/j.dsr.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The community of deep-sea decapod crustaceans between 175 and 2600m in submarine canyons of a volcanic oceanic island (central-eastern Atlantic)

Abstract: Objetivo: Determinar la composición y distribución de los crustáceos de profundidad, capturados con nasas en las ecorregiones Magdalena (MAG), Tayrona (TAY) y Palomino (PAL) del área marina del departamento del Magdalena, Colombia. Alcance: Información base para el manejo de las especies de crustáceos de aguas profundas de potencial importancia comercial. Metodología: Se realizaron cuatro muestreos entre octubre y noviembre de 2016 en las tres ecorregiones, entre los 200 y 500 metros de profundidad, a bordo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 113 publications
0
6
0
1
Order By: Relevance
“…show changes between seasons in each area were less than 0.75 °C and 0.024 PSU for each 50 m in the bathymetric area of distribution ( Figure 9). Related with this, Pajuelo et al (2015) also found that the bathymetric distribution of C. affinis is not linked to a specific water mass with certain conditions of salinity and temperature.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…show changes between seasons in each area were less than 0.75 °C and 0.024 PSU for each 50 m in the bathymetric area of distribution ( Figure 9). Related with this, Pajuelo et al (2015) also found that the bathymetric distribution of C. affinis is not linked to a specific water mass with certain conditions of salinity and temperature.…”
Section: Discussionmentioning
confidence: 62%
“…Related with this, Pajuelo et al. () also found that the bathymetric distribution of C. affinis is not linked to a specific water mass with certain conditions of salinity and temperature.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Una de las especies de mayor abundancia en número de individuos y CPUE promedio fue el camarón P. longipes, coincidiendo con lo encontrado por PAJUELO et al (2015) en el Atlántico centro-oriental (Islas Canarias), quienes encontraron que especies del género Plesionika dominan en la pesca con nasas en comparación con otros métodos de pesca como el arrastre. Otros autores afirman que la familia Pandalidae es muy abundante en aguas profundas del Mar Mediterráneo, el Mar Egeo, las Islas Canarias y Archipiélago de Madeira Atlántico nororiental, siendo Plesionika narval un recurso importante para la pesquería artesanal (ARCULEO et al, 2002;PAJUELO et al, 2015).…”
Section: Discussionunclassified
“…The Canary region is characterized by the presence of three water masses in the first 1000 m of depth, the Eastern North Atlantic Central Water, the Antarctic Intermediate Water, and the Mediterranean Water, located at different depths and with characteristic thermohaline properties (Hernández-Guerra et al 2002). These water masses generate changes in salinity and particularly in temperature, resulting in the presence of density and thermal barriers that affect the distribution of decapod crustacean (Pajuelo et al 2015) and fish species (Pajuelo et al 2016) in the region.…”
Section: Introductionmentioning
confidence: 99%